Rhizoremediation of Cu(II) ions from contaminated soil using plant growth promoting bacteria: an outlook on pyrolysis conditions on plant residues for methylene orange dye biosorption. Issue 1 (1st January 2020) - Yaashikaa, P. R.; Senthil Kumar, P.; Varjani, Sunita; Saravanan, A.
ABSTRACT: Rhizoremediation is one of the most accepted, cost-effective bioremediation techniques focusing on the application of rhizospheric microorganisms in combination with plants for the remediation of organic and inorganic pollutants from the contaminated sites. This work focuses on isolation and identification of metal resistant bacteria to grow on medium with the copper ion concentration of 1500 mg/L. The resistant isolate was identified as Pantoea dispersa by a 16S rRNA sequencing. The bioaccumulation of Cu(II) ions in plant is high at the concentration of Cu(II) ion is 125 mg/L in soil. In Sphaeranthus indicus the Cu(II) ion translocation factor has expanded with an expansion of grouping of Cu(II) ion in the soil and the most extreme TF factor was acquired at the centralization of Cu(II) ion is 150 mg/L in soil. Surface morphology of biochar was characterized by Scanning Electron Microscopy (SEM) analysis. The adsorption performance of biochar ( Sphaeranthus indicus biomass) and mechanism for the removal of Cu(II) ion were investigated. This study resolves that pyrolysis is promising technology for the conversion of metal ion contaminated plant residues from phytoremediation into valuable products. Graphical Abstract: